War as Exit from Exclusion? The Formation of Mayi-Mayi Militias in Eastern Congo - Vlassenroot, Koen; Van Acker, Frank (Afrika Focus, 2001)
In eastern Congo scores of young and marginalized people have been increasingly attracted to the mobilising efforts of new local actors. The inquiry into this phenomenon traces the emergence of the first militias to the end of the eighties. These first generation militias were a result of the growing willingness of marginalized youngsters and school drop-outs to form groups of under-aged combatants acting against eveiy representative of modern political authority and against their desperate feelings of exclusion, for which both their political and social environment were held responsible. As they had nothing more to lose than their marginalisation, rebellion became an option, both as a survival strategy and as a strategy of self-defence against a predatory political and social order. The shiftiness of their ideological basis and allies only further proved what these first militias were about: a search for alternatives to a situation of acute deprivation. This article reveals that the present RCD rebellion that rages through the eastern parts of the Democratic Republic of Congo has had an escalating effect on the proliferation of new militias. Before, the Kabila-led AFDL rebellion had already offered the already existing militias a new cause: that of an anti-Tutsi force fighting against foreign occupation. In resistance to the effects of state collapse and armed foreign interventions, rural and urban youth today have combined former traditions and newly developed patterns of mobility in an interpretation of customary and national defence. This has not meant that they link up with the traditional emanations of authority. Rather, a crisis in the social fabric has meant a shift in authority towards these combatants and the use of violence. In addition, shared feelings of antipathy towards the 'Tutsi-aggressors ' have facilitated the creation of links between these diverse local groupings and other, foreign, factions of armed militia roaming the local countryside. Consolidation, however, remains unlikely as this shared ideology does not run very deep and alliances continuously change. The question remains what the future impact of these militias might be on the local social order. On the one hand, for several years now in some remote areas these armed groupings have become the only representatives of any authority structure, even if this structure is based on violence. Contrary to other cases, these militias in South Kivu are still closely linked to the rural population and have not turned against them. On the other hand, the dynamic of the Inter-Congolese Dialogue has forced their leaders to present their grievances to the outside world. Key Words: Mayi Mayi, militias, politics, rebellion, R.D. Congo